Erratum: Johannessen et al. Work-Related Satisfaction among Clinicians Working at Inpatient Treatment Facilities for Substance Use Disorder: The Role of Recovery Orientation. Int. J. Environ. Res. Public Health 2021, 18, 7423 - Dagny Adriaenssen Johannessen (MDPI AG, 2021)
In the published article [...]